Factors influencing employee commitment through the mediator job satisfaction - a study of office staffs in Ho Chi Minh city - Bui Nguyen Bao Khue (Ho Chi Minh City Open University Journal of Science - Social Sciences, 2017)
This paper examines the relationship between employee-related factors and employee commitment through the mediator job satisfaction of office employees in Ho Chi Minh City. The conceptual model is adapted from previous research and Herzberg’s two-factor theory. The theory emphasized the certain elements belonging to two categories intrinsic and extrinsic value that lead to people’s satisfaction. Four factors include Training, Pay, Working Environment, and Leadership. The data is collected through questionnaires from 422 office staffs in Ho Chi Minh; then only 395 qualified responses are analyzed. SPSS and AMOS tools are used to analyze the data through Reliability test, Model fit test, SEM method. The final result reveals that all factors are significantly related to Job Satisfaction meaning these variables also have indirect positive relationship with Employee commitment through the mediator. This research is useful for organizations which aim to build the commitment strategy for keeping best talents in the company.